Desain UI/UX Aplikasi Mobile LMS dengan Metode Design Thinking untuk Efektifitas Pembelajaran Mahasiswa di Perguruan Tinggi - Bosya Perdana; Tata Sutabri (Jurnal Syntax Admiration, 2024)
This research seeks to develop the UI/UX of the Mobile Learning Management System (LMS) application by utilizing the Design Thinking methodology to improve the effectiveness of student learning in higher education. Design Thinking is used because of its user-centric methodology, guaranteeing that LMS apps align with the preferences and behaviors of students who are increasingly relying on mobile devices in their daily routines. Application development goes through the stages of Empathize, Define, Ideate, Prototype, and Test, with validation carried out using the System Usability Scale (SUS) approach. The assessment involved five students from various academic fields who are proficient in desktop-based Learning Management Systems (LMS). The test results showed a SUS score of 78, categorized as "Good" and close to "Very Good". This score signifies the program's excellent usability, easy navigation, and functions that encourage learning flexibility, including content access, assignment submission, and discussion forums. This study shows that the mobile Learning Management System created using the Design Thinking methodology significantly increases student access to lecture materials and encourages the efficacy of learning in higher education. Suggestions for improvements include conducting assessments with a wider group of participants and implementing design iterations to refine features based on user feedback.